Synthesis and thermal degradation mechanism of polyorganocarboranesiloxanes containing m-carboranylmethyl unit. (October 2017) - Lou, Pingping; Zhang, Xuezhong; Liu, Bozheng; Gao, Xiyin; Zhang, Zhijie; Xie, Zemin
Abstract: This paper reports a high-yielding, efficient and facile method in preparing monomers, namely 1, 7-bis(hydroxyl(dimethyl)silylmethyl)- m -carborane (M1 ), 1, 7-bis(diethylamino(dimethyl)silylmethyl)- m- carborane (M2 ), 1, 3-dimethyl-1, 3-diphenyl-siloxanediol (M3 ) and diethylaminomethylphenylsilane (M4 ). The reaction ofM2 andM3 to get polymerP1, and the reaction ofM1 andM4 to get polymerP2 which has a promising lead in searching for materials with high-temperature properties. The structure of monomers and linear polymers were characterized by NMR and FTIR. Thermal properties of the polyorganocarboranesiloxane elastomers were characterized by DSC and TGA. The results showed that elastomersE1 andE2 have better thermal stability and thermal oxidative stability with 5% weight loss temperatures above 570 °C, 650 °C in nitrogen and 536 °C, 730 °C in air, respectively than that of linear polymersP1 andP2 . The highlight was to study the thermal degradation mechanism of polyorganocarboranesiloxane elastomers using XPS and Solid-state 29 Si NMR. Carborane and organosiloxane outside of samples were gradually oxidized to B2 O3 and SiO2 respectively, the inside only occurred the cleavage of the Si-Ph bond caused by terminal hydroxyl groups which resulted in chain branching and illustrated there was no access for oxygen easy to internal oxidation.